Overcoming the identity crisis in human resources. Issue 2 (4th March 2014) - Flynn, Stephen
Abstract : Purpose: – Dissects "partnership" and "strategy" in the context of the work of HR. Design/methodology/approach: – Shows that it is not that HR is unclear about its role in the corporate world but that the exhortations of commentators are too simplistic. Findings: – Reveals that the continuing and continual debate over HR's role is a product of the role conflict inherent in the HR profession itself. Emphasizes the importance of balancing the needs of employees with those of managers, which is at the heart of HR. Practical implications: – Contends that divorcing the operational from the strategic denies the strategic the field intelligence that informs and proves strategy. The disparate, mundane operational tasks associated with HR specialists aggregate into the field intelligence that feeds their strategic perspective. Severing the connection between HR strategy and HR operations impoverishes any kind of strategic input available to HR. Social implications: – Advances the view that managers and employees see their day-to-day requests as important and that these apparently mundane matters are the nuggets that inform HR's strategic input. Originality/value: – Emphasizes that there is an organizational and employee aspect to every element of HR and that the HR specialist should accept both of these.